Prolonged estrogen deprivation triggers a broad immunosuppressive phenotype in breast cancer cells. Issue 1 (29th August 2021) - Hühn, Daniela; Martí‐Rodrigo, Pablo; Mouron, Silvana; Hansel, Catherine; Tschapalda, Kirsten; Porebski, Bartlomiej; Häggblad, Maria; Lidemalm, Louise; Quintela‐Fandino, Miguel; Carreras‐Puigvert, Jordi; Fernandez‐Capetillo, Oscar
Abstract : Among others, expression levels of programmed cell death 1 ligand 1 (PD‐L1) have been explored as biomarkers of the response to immune checkpoint inhibitors in cancer therapy. Here, we present the results of a chemical screen that interrogated how medically approved drugs influence PD‐L1 expression. As expected, corticosteroids and inhibitors of Janus kinases were among the top PD‐L1 downregulators. In addition, we identified that PD‐L1 expression is induced by antiestrogenic compounds. Transcriptomic analyses indicate that chronic estrogen receptor alpha (ERα) inhibition triggers a broad immunosuppressive program in ER‐positive breast cancer cells, which is subsequent to their growth arrest and involves the activation of multiple immune checkpoints together with the silencing of the antigen‐presenting machinery. Accordingly, estrogen‐deprived MCF7 cells are resistant to T‐cell‐mediated cell killing, in a manner that is independent of PD‐L1, but which is reverted by estradiol. Our study reveals that while antiestrogen therapies efficiently limit the growth of ER‐positive breast cancer cells, they concomitantly trigger a transcriptional program that favors their immune evasion. Abstract : Under prolonged hormone therapy, ER + breast cancer cells activate an inflammatory transcriptional program, which includes a generalized upregulation of immune checkpoint mediators together with the downregulation of the antigen‐presenting machinery. These findings reveal that, while hormone therapies efficiently arrest the growth of ER + breast cancer cells, they also promote a phenotype switch that favors their immune evasion.